The Development of Minangkabau Women's Electability in the Indonesian House of Representatives: An Analysis of the 2019 Legislative Election Turning Point - Hasri Ainun Mahalli; Mudiyati Rahmatunnisa; Sri Zul Chairiyah (Green Publisher Indonesia, 2026)
The electability of Minangkabau women in the House of Representatives has shown inconsistent development since the beginning of the post-reform democratic period, despite women holding an important role in the Minangkabau matrilineal cultural structure. Historically, West Sumatra has been among the provinces with the lowest levels of female representation in the House of Representatives. From the 1999 to 2014 general elections, no more than one woman was elected in any single term, and in some election periods no woman managed to gain a seat in parliament. However, the 2019 legislative elections marked the most significant change in two decades: three Minangkabau women won seats simultaneously, the highest number recorded since the reform era. This research aims to trace the historical development of Minangkabau women's electability from 1999 to 2019 and to analyse the key factors that enabled their electoral breakthrough in the 2019 legislative elections. Using a literature-based qualitative approach, this article traces the development of Minangkabau women's electability across this period and examines the factors that enabled the breakthrough in 2019. The findings show that the increase in the success of female candidates in 2019 was primarily driven by access to political capital — such as elite networks and party support — and strong social capital resources associated with community legitimacy and family reputation. This research concludes that matrilineal status does not necessarily translate into electoral gains for women, and that sustainable political representation relies heavily on structural, partisan, and resource-based dynamics.